La Transnistrie, la mondialisation paradoxale d’un État non reconnu - Thomas Merle (L'Espace Politique)
The economic globalization has spread almost all over the world. Even the States with limited recognition, though they cannot sign treaties with other States or join supranational organizations such as the WTO, are involved in this process. Transnistria, a State with limited recognition which have seceded from Moldova with the support of Russia in the early 1990’s, is an interesting case to show the adaptation strategies of an unrecognized entity to integrate into the globalization. The Russian geopolitical and geoconomical power is not only a key factor for the existence of Transnistria but also for its globalization. How can Transnistria be a closed entity from the (geo)political point of view but so highly opened from the economic point of view that it is very sensitive to the global economic crisis? The study, based on a field work and on statistical analysis, focuses on the steel industry, leading sector of the entity which accounted for more than half of the GDP of Transnistria at the end of the USSR; this sector was significantly impacted since 2007, inducing the political authorities to react in order to ensure their own survival.